1997
DOI: 10.1007/bf00419767
|View full text |Cite
|
Sign up to set email alerts
|

Interrupting intentions: Zeigarnik-like effects in prospective memory

Abstract: In two experiments, we examined the effects of task interruption on memory for intentions. Participants studied a series of anagrams, of which they solved one-half (Exp. 1) or two-thirds (Exp. 2), whereas the solution of the remaining items was interrupted by the experimenter. Furthermore, four anagrams (prospective cue items) differed from the remaining anagrams in that the third letter of each item was underlined. Participants were instructed to decide whether a subsequently presented (target) anagram contai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
21
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 24 publications
3
21
0
Order By: Relevance
“…For example, in the study of Zeigarnik (1927) participants were interrupted by the experimenter half way through a task(s) (see also Mäntylä & Sgaramella, 1997). In the present study, there was no external agent interrupting an ongoing activity when children encountered a target picture of an animal.…”
Section: Prospective Memory In Childrenmentioning
confidence: 72%
“…For example, in the study of Zeigarnik (1927) participants were interrupted by the experimenter half way through a task(s) (see also Mäntylä & Sgaramella, 1997). In the present study, there was no external agent interrupting an ongoing activity when children encountered a target picture of an animal.…”
Section: Prospective Memory In Childrenmentioning
confidence: 72%
“…For example, inadvertently taking certain medication twice can be highly dangerous for the individual. Once an intention has been realized, the memory for the intended action vanishes, an effect known as the Zeigarnik effect (Zeigarnik, 1927; Mäntylä and Sgaramella, 1997). Upon completion of an intention, the monitoring of the environment for cues that are associated with the intended action, is discontinued (Scullin et al, 2009; Beck et al, 2014), which is associated with the deactivation of brain areas that are engaged in monitoring processes during the active phase of the intention (Beck et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Few studies have directly addressed the influence on PM of an unexpected, external interruption, such as a person-initiated interruption unrelated to the ongoing task (Mantyla & Sgaramella, 1997;McDaniel, Einstein, Graham, & Rall, 2004). Early work on how PM performance may be affected by an interruption was conducted by Mantyla and Sgaramella (1997).…”
Section: Introductionmentioning
confidence: 99%
“…Early work on how PM performance may be affected by an interruption was conducted by Mantyla and Sgaramella (1997). These authors reported that cue items associated with interruption were better reminders than were items that were associated with completion.…”
Section: Introductionmentioning
confidence: 99%